Interpreting research in South Africa: A bibliometric study - Kotzé, Herculene (Stellenbosch Papers in Linguistics Plus, 2020)
After South Africa’s transition to democracy in 1994, there was an expectation that problems related to translation services would receive more attention, especially given the fact that 11 languages received official status after 1994 (Lubbe 2002:78). In addition, the call to transform and decolonize South Africa has led to widespread discussion regarding which steps need to be taken to strengthen the African perspective in higher education. Kotzé and Wallmach (forthcoming) offer an in-depth look at research trends on interpreting in South Africa for the period 2006 to 2016. They highlight that, in order to transform South African interpreting studies, it is essential to know what has already been researched and, going forward, what we can learn from publication trends on interpreting. By using a systematic literature review (Fink 2005), this bibliometric study investigates the trends of interpreting research done in South Africa, from the first publication found in 1968, through to 2017. The findings from this study will be of value to current and future interpreting researchers in that they will highlight current trends and shortcomings in South African interpreting research, and contribute to understanding and solving issues of transformation within this specific field.